2014
DOI: 10.1186/1471-2369-15-71
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fibroblast growth factor 23 levels in normophosphatemic patients with chronic kidney disease stage 3 treated with lanthanum carbonate: results of the PREFECT study, a phase 2a, double blind, randomized, placebo-controlled trial

Abstract: BackgroundHigh levels of circulating fibroblast growth factor 23 (FGF23) are associated with chronic kidney disease (CKD) progression and high mortality. In the Phosphate Reduction Evaluation of FGF23 in Early CKD Treatment (PREFECT) study, we assessed the effect of reducing intestinal phosphate absorption using lanthanum carbonate on FGF23 levels in normophosphatemic patients with CKD stage 3.MethodsThirty-five individuals were randomized to lanthanum carbonate 3000 mg/day (n = 23) or placebo (n = 12) for 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…Actually, the latter observation is true only if we consider globally the phosphate binders tested: indeed, in this study, sevelamer carbonate significantly reduced intact FGF23, but calcium acetate increased it, whereas patients receiving lanthanum carbonate did not show any difference compared with the placebo group. These results are confirmed by Ureña-Torres et al who reported no sustained decrease in intact FGF23 concentrations in normophosphatemic patients with stage 3 CKD treated with lanthanum carbonate [23]. Moreover, Nagano et al have previously demonstrated that sevelamer hydrochloride reduced serum phosphorus and subsequently FGF23 levels in rats with chronic renal failure [24].…”
Section: Expert Opinionsupporting
confidence: 77%
“…Actually, the latter observation is true only if we consider globally the phosphate binders tested: indeed, in this study, sevelamer carbonate significantly reduced intact FGF23, but calcium acetate increased it, whereas patients receiving lanthanum carbonate did not show any difference compared with the placebo group. These results are confirmed by Ureña-Torres et al who reported no sustained decrease in intact FGF23 concentrations in normophosphatemic patients with stage 3 CKD treated with lanthanum carbonate [23]. Moreover, Nagano et al have previously demonstrated that sevelamer hydrochloride reduced serum phosphorus and subsequently FGF23 levels in rats with chronic renal failure [24].…”
Section: Expert Opinionsupporting
confidence: 77%
“…However, the effect of phosphorus intake on FGF23 appears to be modest in human studies, with some studies unable to detect a significant effect (19, 32, 48, 78, 79, 94, 111, 161, 165). Recent human studies suggest that PTH rather than FGF23 explains the increased phosphaturia that occurs immediately after an acute phosphorus load (137).…”
Section: Phosphorus Metabolism In Healthmentioning
confidence: 99%
“…This link was demonstrated with a 42% mortality reduction in association with phosphate binder therapy in the well-known ArMORR study in incident dialysis patients (n = 8610) [8]. Recent studies aim toward measurement of alternate biomarkers, such as FGF-23 [47], and its relationship to hyperphosphatemia, as well as the use of phosphate binder therapy in the stage 3 and 4 CKD population [48][49][50]. Some of these studies have demonstrated that treatment with non-calcium-based phosphate binders, such as lanthanum carbonate, is associated with reductions of serum FGF-23 [48], and similar results have been observed with sucroferric oxyhydroxide [51].…”
Section: Future Perspectivementioning
confidence: 92%